Prospects for rambutan peel extract as natural antioxidant on the aging properties of vulcanized natural rubber. (5th May 2021) - Sukatta, Udomlak; Rugthaworn, Prapassorn; Seangyen, Wichudaporn; Tantaterdtam, Rattana; Smitthipong, Wirasak; Chollakup, Rungsima
Abstract: Natural rubber (NR) is sensitive to oxidative degradation, which needs to add commercial antioxidant for NR compounding to improve its aging properties. The aim of this study is to apply natural antioxidant obtained from extracted rambutan peel powder (RE) by methanol compared to commercial antioxidants for NR compounding in a conventional vulcanization (CV system). Two types of commercial antioxidants were N‐(1, 3‐dimethylbutyl)‐N'phenyl‐p‐phenylenediamine (6PPD) and 2, 2, 4‐Trimethyl‐1, 2dihydroquinoline (TMQ). The main phenolic compounds in RE were geraniin, corilagin, ellagic acid and gallic acid which had greater antioxidant activity based on all methods, especially for 2, 2‐Diphenyl‐2‐picrlhydrazyl radical‐scavenging assay (DPPH) and had a similar antioxidant activity to 6PPD. The antioxidants were applied in NR vulcanizates at 1 phr and 2 phr to study their physical and mechanical properties. The decomposition temperature of RE was higher than for 6PPD but similar to TMQ. The decomposition temperature of the rubber vulcanizates containing RE was higher than for the commercial antioxidants. Rubber vulcanizates with RE retained similar tensile strength and modulus at 100% strain as the commercial antioxidants. Furthermore, the addition of RE in rubber vulcanizates helped to resist thermal aging at 70°C and ozone aging, particularly at 1 phr at least as well as in the commercial antioxidants. Therefore, RE can be used as an alternative natural antioxidant in natural rubber to replace commercial antioxidants. Abstract :